Máquina Museu - Vítor Oliveira Jorge (Midas: Museus e Estudos Interdisciplinares)
Brief and general critical reflection on the “museum” reality and what it implies as a total social phenomenon, typical of modernity. The museum’s civic responsibility as an inescapable ideological-political instrument. The museum contains in itself, or symbolizes, all the paradoxes of modernity and, with it, of Western ontology itself: it objectifies, it exposes to our scopic and fetishist drive a kind of microcosm, a representative collection of some idea, but, like the collection, it is never complete: the imaginary and the symbolic that the museum embodies are never enough, we always leave the visit with a sense of incompleteness. But it's a good thing that the museum is an imperfect machine: in a functionalized world, it is the modern temple where one does nothing, only contemplates or essentially meditates.